2011
DOI: 10.1002/jsfa.4655
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous mammalian sex hormones mitigate inhibition in growth by enhancing antioxidant activity and synthesis reactions in germinating maize seeds under salt stress

Abstract: Exogenous MSH application was found to have an important ameliorative effect on growth of seeds exposed to salt stress by stimulating antioxidant activity and synthesis reactions. This is the first study investigating the effects of MSH on germination of seeds exposed to stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 25 publications
(31 reference statements)
0
24
0
2
Order By: Relevance
“…Ion homeostasis and osmotic regulation play crucial roles in maintaining metabolic processes and cell turgidity . Changes in these parameters are important for determining the level of plant stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion homeostasis and osmotic regulation play crucial roles in maintaining metabolic processes and cell turgidity . Changes in these parameters are important for determining the level of plant stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…High salinity is among the most detrimental of abiotic stresses, and it causes serious dysfunction in many vital processes, from the structural changes in membranes to major metabolic reactions such as photosynthesis, protein synthesis, and energy metabolism . Many researchers have described in detail the morphological and metabolic changes arising from high salinity for a number of plant species during all growth and developmental stages, from germination through florescence . In addition, these studies revealed that plants have developed many defence strategies to tolerate the harmful effects of exposure to salt stress, including elevating the levels of osmo‐regulators such as proteins, carbohydrates and proline; activating the enzymatic and non‐enzymatic antioxidant systems; and maintaining ion homeostasis and the cellular redox status .…”
Section: Introductionmentioning
confidence: 99%
“…Soil salinization is a serious problem in agriculture worldwide. Salinity is threatening about 20% of cultivated soil and 50% of irrigated land around the world . Several studies have been conducted to investigate the mechanism of plant response to salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is threatening about 20% of cultivated soil and 50% of irrigated land around the world. 1,2 Several studies have been conducted to investigate the mechanism of plant response to salinity. Salinity imposes ion toxicity, decreases soil's osmotic potential and creates a water stress for plants.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that MSHs act as endocrine disruptors in aquatic animals, a number of studies have demonstrated their beneficial effects on plants coping with abiotic stresses [3]- [9]. Progesterone, 17β-estradiol and androsterone applications mitigated the effects of salinity stress by enhancing germination rate, and root and shoot length in maize [6] and wheat seedlings [7]. The protective effect of MSHs has also been reported in the case of chilling and heavy metal stresses [8] [9].…”
Section: Introductionmentioning
confidence: 99%